An Energy Management Strategy to concurrently optimise fuel consumption & PEM fuel cell lifetime in a hybrid vehicle. (14th December 2016) - Fletcher, Tom; Thring, Rob; Watkinson, Martin
Abstract: The cost and reliability of fuel cells are major obstructions preventing fuel cell hybrid electric vehicle (FCHEV) from entering the mainstream market. However, many of the degradation methods are strongly affected by the operating conditions of the fuel cell and therefore can be mitigated by optimisation of the Energy Management Strategy (EMS). The major causes of fuel cell degradation are identified from the literature and a model is produced in order to estimate the effect of the EMS on the fuel cell degradation. This is used to produce an optimal strategy for a low speed campus vehicle using Stochastic Dynamic Programming (SDP). The SDP controller attempts to minimise the total running cost of the fuel cell, inclusive of both fuel consumption and degradation, each weighted by their respective costs. The new strategy is shown to increase the lifetime of the fuel cell by 14%, with only a 3.5% increase in fuel consumption, largely by avoiding transient loading on the fuel cell stack. Highlights: Fuel consumption & cell ageing are concurrently optimised for fuel cell vehicles. Quantitative analysis of total running cost inclusive of cell degradation. Baseline controller is optimised purely on fuel consumption. Just 3.5% increase in fuel consumption compared to baseline. A 14% increase in lifetime is projected and 7% reduction in overall running cost.